Pengaruh Digital Marketing, Electronic Word of Mouth (E-Wom), dan Perceived Quality Terhadap Keputusan Pembelian Konsumen pada Produk Keripik “UMKM Intan Rahmadhani Snack” - Adhwa Syafaa Kamila; Titik Desi Harsoyo (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of digital marketing, electronic word of mouth (E-WOM), and perceived quality on consumer purchasing decisions on Intan Rahmadhani Snack UMKM chips products in Yogyakarta. The sampling technique used purposive sampling with a sample size of 100 respondents who had purchased UMKM Intan Rahmadhani Snack chips products. The data analysis method used Multiple Linear Regression analysis. The results of this study prove that Digital Marketing, Electronic Word of Mouth (E-WOM), and Perceived Quality has a positive and significant effect on Consumer Purchasing Decisions on Intan Rahmadhani Snack UMKM Chips Products.